If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4t + -2) + 7t = 4t + -4 Reorder the terms: -3(-2 + 4t) + 7t = 4t + -4 (-2 * -3 + 4t * -3) + 7t = 4t + -4 (6 + -12t) + 7t = 4t + -4 Combine like terms: -12t + 7t = -5t 6 + -5t = 4t + -4 Reorder the terms: 6 + -5t = -4 + 4t Solving 6 + -5t = -4 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 6 + -5t + -4t = -4 + 4t + -4t Combine like terms: -5t + -4t = -9t 6 + -9t = -4 + 4t + -4t Combine like terms: 4t + -4t = 0 6 + -9t = -4 + 0 6 + -9t = -4 Add '-6' to each side of the equation. 6 + -6 + -9t = -4 + -6 Combine like terms: 6 + -6 = 0 0 + -9t = -4 + -6 -9t = -4 + -6 Combine like terms: -4 + -6 = -10 -9t = -10 Divide each side by '-9'. t = 1.111111111 Simplifying t = 1.111111111
| 6x-27=4x+12 | | cx+5=dx-3 | | 5+2(x+1)=2n | | 9y+13=30 | | w^2-11=2-5w^2 | | 6x+40=8x-20 | | 5*x+2=11-x*8 | | 4b-8=1+6-3b-1 | | 2x^2+kx^2-2kx-16=0 | | 2x-(x+2)=2x-0.1 | | 6=7x-x+6 | | w*w+9=6w | | 4x+172=180 | | .3T-2.1C-2.3=7.6 | | 5r+4=9(r-3) | | (m/2)-(1/m)=(6m+5/12) | | X^2+6X=34 | | 15x-75=90 | | Y=(15x+10)(15x-2) | | 3(2a-b)-5a= | | 7v+2=0 | | 2x-4x+4=x-3+7 | | 7=3(t-5)-t | | 3x^2-2x-8=448 | | Y=225x^2+120x+20 | | 1.3x+1.6y=.6 | | 15x-150=90 | | -8-2(8n-8)=-6n+8 | | 5x-2x-3=27 | | -76+n=-115 | | 6tx=4+2 | | 5x-6+6/5=14+6/5 |